Understanding the carbon-monoxide oxidation mechanism on ultrathin palladium nanowires: a density functional theory study. Issue 4 (24th December 2015) - Yang, Po-Yu; Ju, Shin-Pon; Lai, Zhu-Min; Lin, Jenn-Sen; Hsieh, Jin-Yuan
Abstract : The CO oxidation mechanism catalyzed by ultrathin helical palladium nanowires (PdNW) was investigated by density functional theory (DFT) calculation. Abstract : The CO oxidation mechanism catalyzed by ultrathin helical palladium nanowires (PdNW) was investigated by density functional theory (DFT) calculation. The helical PdNW structure was constructed on the basis of the simulated annealing basin-hopping (SABH) method with the tight-binding potential and the penalty method in our previous studies ( J. Mater. Chem., 2012, 22, 20319). The low-lying adsorption configurations as well as the adsorption energies for O2 and CO molecules on different PdNW adsorption sites were obtained by DFT calculation. The most stable adsorption configurations for the Langmuir–Hinshelwood (LH) mechanism processes were considered for investigating the CO oxidation mechanism. The nudged elastic band (NEB) method was adopted to obtain the transition state configuration and the minimum energy pathways (MEPs).